Respostas
respondido por:
1
f(x) = 3x³ - 1
f(0) = 3(0) - 1
f(0) = - 1
f(-1) = 3(- 1)³ - 1
= 3(-1) - 1
= -3 - 1
f(- 1) = - 4
f(1/2) = 3(1/2)³ - 1
= 3(1/8) - 1
= 3/8 - 1
= 3/8 - 8/8
f(1/2) = - 5/8
f(0) + f(- 1) + f(1/2) = - 1 - 4 - 5/8
= - 5 -5/8
= - 1/8(40 + 5)
= - 45/8 RESULTADO FINAL
= - 5 5/8 RESULTADO FINAL
duhh322:
Cara valeu mesmo.. Você não tem noção de quanto me Ajudou o///////
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás